1998
DOI: 10.1021/np9800506
|View full text |Cite
|
Sign up to set email alerts
|

Epolones:  Novel Sesquiterpene-Tropolones from Fungus OS-F69284 That Induce Erythropoietin in Human Cells

Abstract: In the course of our screening for small molecule modulators of erythropoietin gene expression, two novel sesquiterpene tropolones and pycnidone were isolated from a culture of OS-F69284 (ATCC 74390). Their structures were elucidated by extensive 1H and 13C NMR spectroscopic studies and chemical reactions. These compounds induced erythropoietin gene expression 5-fold at a concentration of 1-1.6 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 6 publications
5
57
0
7
Order By: Relevance
“…Pycnidione (180), [87] eupenifeldin (181), [88] and epolone B (182) [89] are a group of recently isolated fungal metabolites that possess identical tropolone rings attached to a sesquiScheme 35. Biosynthetic studies on culantraramine (167).…”
Section: Pycnidione and Othersmentioning
confidence: 99%
“…Pycnidione (180), [87] eupenifeldin (181), [88] and epolone B (182) [89] are a group of recently isolated fungal metabolites that possess identical tropolone rings attached to a sesquiScheme 35. Biosynthetic studies on culantraramine (167).…”
Section: Pycnidione and Othersmentioning
confidence: 99%
“…Green tea catechin EGCG increases the level of nuclear HIF-1a protein and activates the expression of HIF-1 downstream genes . The structurally related fungal sesquiterpenes pycnidione, epolone A, and epolone B induce erythropoietin expression via HIF-1a activation (Cai et al, 1998;Wanner et al, 2000). In a study of cultured dorsal root ganglia, it was found that neuronal NO induces the HIF-1-dependent expression of erythropoietin in adjacent Schwann cells, and the erythropoietin in turn protects axons of the neurons against neurotoxin-induced degeneration (Keswani et al, 2011).…”
mentioning
confidence: 99%
“…Representative structures of fungi are puberulic acid, puberulonic acid, stipitatic acid and related structures (Corbett et al, 1950;Iwatsuki et al, 2011). More complex known compounds are epolone A or B, pycnidione, eupenifeldin or fusariocin C (Ito et al, 1981;Mayerl et al, 1993;Cai et al, 1998), which structurally share the fused tropolone/dihydropyran ring structure with the malettinins. However, malettinins 1-4 are unique with regard to their linkage of the tropolone/dihydropyran ring to a furan.…”
Section: Discussionmentioning
confidence: 99%